2017
DOI: 10.1113/jp274059
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal nicotine exposure impairs the maturation of glutamatergic inputs in the auditory brainstem

Abstract: Key pointsr Chronic perinatal nicotine exposure causes abnormal auditory brainstem responses and auditory processing deficits in children and animal models.r The effect of perinatal nicotine exposure on synaptic maturation in the auditory brainstem was investigated in granule cells in the ventral nucleus of the lateral lemniscus, which receive a single calyx-like input from the cochlear nucleus.r Perinatal nicotine exposure caused a massive reduction in the amplitude of the excitatory input current.r This caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
(156 reference statements)
3
16
0
Order By: Relevance
“…The biophysical activity pattern of P9/10 and mature neurons in the ventral nucleus of the lateral lemniscus (VNLL), medial nucleus of the trapezoid body (MNTB), medial superior olive (MSO) and dorsal nucleus of the lateral lemniscus (DNLL) are established from long step current injections (Banks and Smith, 1992;Forsythe, 1994;Ahuja and Wu, 2000;Scott et al, 2005;Chirila et al, 2007;Porres et al, 2011;Ammer et al, 2012;Franzen et al, 2015;Baumann and Koch, 2017). Our comparative data corroborated the described onset action potentials in MNTB, MSO, and VNLL neurons and the continuous firing from DNLL neurons (Figure 1).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The biophysical activity pattern of P9/10 and mature neurons in the ventral nucleus of the lateral lemniscus (VNLL), medial nucleus of the trapezoid body (MNTB), medial superior olive (MSO) and dorsal nucleus of the lateral lemniscus (DNLL) are established from long step current injections (Banks and Smith, 1992;Forsythe, 1994;Ahuja and Wu, 2000;Scott et al, 2005;Chirila et al, 2007;Porres et al, 2011;Ammer et al, 2012;Franzen et al, 2015;Baumann and Koch, 2017). Our comparative data corroborated the described onset action potentials in MNTB, MSO, and VNLL neurons and the continuous firing from DNLL neurons (Figure 1).…”
Section: Resultssupporting
confidence: 83%
“…Often observed is a developmental drop in input resistance (Magnusson et al, 2005;Scott et al, 2005;Chirila et al, 2007;Hoffpauir et al, 2010;Rusu and Borst, 2011;Franzen et al, 2015Franzen et al, , 2020 based on the upregulation of ion channels (Scott et al, 2005;Hassfurth et al, 2009;Khurana et al, 2012;Franzen et al, 2015). In this developmental period synaptic current accelerates by changes in AMPA receptors (Bellingham et al, 1998;Taschenberger and von Gersdorff, 2000;Joshi and Wang, 2002;Koike-Tani et al, 2005;Youssoufian et al, 2005;Ammer et al, 2012;Felix and Magnusson, 2016;Baumann and Koch, 2017;Franzen et al, 2020) and a reduction or loss of synaptic NMDA receptors (Bellingham et al, 1998;Steinert et al, 2010;Case et al, 2011;Hirtz et al, 2011;Ammer et al, 2012;Winters and Golding, 2018;Franzen et al, 2020). The neuronal morphology remodels by changes in the dendritic arbor (Sanes et al, 1992;Rietzel and Friauf, 1998;Rautenberg et al, 2009) and somatic size (Franzen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus cholinergic input likely aids in establishing robust connections. Consistent with this notion, a recent study demonstrated that disruption of ␣ 7 -nAChR signaling during VNLL development leads to delays of the maturation of temporal processing (Baumann and Koch 2017). We found that ␣ 7 -receptor KO mice contained SPON and VNLL neurons that exhibited degraded temporal processing.…”
Section: Temporal Deficits In ␣ 7 -Ko Mice Arise Early In the Centralsupporting
confidence: 88%
“…Cholinergic signaling, particularly during development, is important for establishing precise temporal properties of auditory neurons (Baumann and Koch 2017). In other neural systems apart from audition, the ␣ 7 -nAChR is critical for establishing glutamatergic synapses during development (Halff Fig.…”
Section: Temporal Deficits In ␣ 7 -Ko Mice Arise Early In the Centralmentioning
confidence: 99%
See 1 more Smart Citation